Distant interaction of rock mass clusters around underground opening - Griniov, V.; Zakharova, L.; Diedich, I.; Nazymko, V. (Розробка родовищ, 2017)
Purpose. To experimentally prove the fact of distant interaction between rock clusters during the irreversible displacements of rock mass. Disintegration of the rock mass does not necessarily imply loss in underground working stability. Findings. This experiment has demonstrated that the boundary of the rock mass failure expands asynchronously by spatially and temporally discrete increments. Such mechanism of the rock failure zone development is the consequence of the minimum entropy production principle according to which dissipative structures can occur in open thermodynamic systems. Мета. Експериментально довести наявність дальньої взаємодії породних кластерів під час необоротних зрушень масиву гірських порід. Дезінтеграція масиву гірських порід не обов’язково тягне за собою втрату стійкості підземної виробки. Результати. Даний експеримент продемонстрував, що границі зруйнованого масиву розширюються асинхронно, прирощуючи зону руйнування окремими порціями у просторі й часі. Такий механізм розвитку зони зруйнованих порід є наслідком закону про мінімум виробництва ентропії, який стверджує, що у відкритих термодинамічних системах можуть виникати дисипативні структури. Цель. Экспериментально доказать наличие дальнего взаимодействия породных кластеров во время необратимых сдвижений массива горных пород. Дезинтеграция массива горных пород не обязательно влечет за собой потерю устойчивости подземной выработки. Результаты. Данный эксперимент продемонстрировал, что границы разрушенного массива расширяются асинхронно, приращивая зону разрушения отдельными порциями в пространстве и времени. Такой механизм развития зоны разрушенных пород является следствием закона о минимуме производства энтропии, который утверждает, что в открытых термодинамических системах могут возникать диссипативные структуры.